PENGARUH PENDIDIKAN KARAKTER TERHADAP KEJUJURAN PESERTA DIDIK DI MTs AL MURAHAMATUL ISLAMIYAH BANYORANG KABUPATEN BANTAENG - Alifka Tasya, Nurrislami; Rusmin B, Muhammad; Sahib, Amin; Yahdi, Muhammad; Mosiba, Risna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the issue of students’ honesty, which remains a challenge despite the implementation of character education in schools. The research aims to describe the implementation of character education, examine the level of students’ honesty, and analyze the effect of character education on students’ honesty at MTs Al Murahamatul Islamiyah Banyorang, Bantaeng Regency. This study employed a quantitative ex post facto design using simple linear regression analysis. The population consisted of 73 students, and all were selected as the sample through a saturated sampling technique. Data were collected using questionnaire instruments and analyzed through descriptive and inferential statistics. The findings revealed that both character education and students’ honesty were categorized at a moderate level, each with a percentage of 68.49%. Furthermore, the hypothesis testing showed that the calculated t-value (1.998) was higher than the t-table value (1.666), indicating that character education has a positive effect on students’ honesty, although the influence is relatively low at 5.3%, while the remaining 94.7% is influenced by other factors. These results suggest that character education contributes to shaping honest behavior among students; however, its effectiveness needs to be strengthened through consistent practice, role modeling, and integration into school culture. Therefore, improving the quality and implementation of character education is essential to foster higher levels of honesty among students